Helicobacter pylori and Epstein-Barr virus infection in cell polarity alterations - Baral, Budhadev; Kandpal, Meenakshi; Ray, Anushka; Jana, Ankit; Yadav, Dhirendra Singh; Sachin, Kumar; Mishra, Amit; Baig, Mirza S; Jha, Hem Chandra (Folia microbiologica, 2024)
The asymmetrical distribution of the cellular organelles inside the cell is maintained by a group of cell polarity proteins. The maintenance of polarity is one of the vital host defense mechanisms against pathogens, and the loss of it contributes to infection facilitation and cancer progression. Studies have suggested that infection of viruses and bacteria alters cell polarity. Helicobacter pylori and Epstein-Barr virus are group I carcinogens involved in the progression of multiple clinical conditions besides gastric cancer (GC) and Burkitt's lymphoma, respectively. Moreover, the coinfection of both these pathogens contributes to a highly aggressive form of GC. H. pylori and EBV target the host cell polarity complexes for their pathogenesis. H. pylori-associated proteins like CagA, VacA OipA, and urease were shown to imbalance the cellular homeostasis by altering the cell polarity. Similarly, EBV-associated genes LMP1, LMP2A, LMP2B, EBNA3C, and EBNA1 also contribute to altered cell asymmetry. This review summarized all the possible mechanisms involved in cell polarity deformation in H. pylori and EBV-infected epithelial cells. We have also discussed deregulated molecular pathways like NF-κB, TGF-β/SMAD, and β-catenin in H. pylori, EBV, and their coinfection that further modulate PAR, SCRIB, or CRB polarity complexes in epithelial cells.
Keywords: Cell Polarity; Epstein-Barr Virus Infections; koinfekce; Coinfection; virus Epsteinův-Barrové; Humans; Helicobacter pylori; lidé; infekce virem Epsteina-Barrové; Helicobacter Infections; polarita buněk; Herpesvirus 4, Human; nádory žaludku; Stomach Neoplasms; infekce vyvolané Helicobacter pylori; Viral Proteins; virové proteiny